Blended Learning: A Comprehensive Review of Recent Insights and Challenges - Khawlah Ahmed (Journal of Research in Education and Pedagogy, 2025)
As education evolves alongside rapid technological advancements, blended learning (BL) has emerged as a key pedagogical approach that combines traditional face-to-face instruction with online components. This integration aims to create flexible, personalized, and dynamic learning environments. Grounded in constructivist learning theory, this study employs a qualitative approach, analyzing existing literature and post-pandemic developments to assess the benefits and challenges of BL in higher education. The findings underscore the transformative potential of BL in enhancing student engagement, improving learning outcomes, and fostering greater autonomy. However, the study also highlights persistent challenges such as technological barriers, unequal access to digital tools, and gaps in digital literacy among both students and faculty. Effective implementation of BL depends on thoughtful instructional design, strong alignment between delivery modes, and the use of active learning strategies such as collaborative projects, discussion forums, and multimedia integration. Institutional support, including reliable technological infrastructure, professional development, and scaffolded learning opportunities, is crucial to address these challenges and ensure inclusivity. The study also calls for future research into the long-term impact of BL on academic performance, learner motivation, retention, and psychological well-being. Emerging technologies like artificial intelligence (AI), virtual reality (VR), and learning analytics offer promising tools to enhance the personalization, adaptability, and scalability of BL environments. However, their integration demands deliberate policy planning, ethical oversight, and sustained investment. For educators, instructional designers, and policymakers, this study provides actionable insights that can be used to inform curriculum development, strategic planning, and institutional readiness for future educational models.